The strategic motivation factors for it outsourcing decisions in the banking sector - Gadiaga, Mamadou (2021)
Outsourcing is the fact of delegating the supply of a given service to an external organization. This phenomenon is a widespread strategy in the corporate business world. The outsourcing of information technology in the banking sector has particularly called our attention. Banking activity is highly dependent on the information technology (IT) process. Banks opt for an Information Technology Outsourcing (ITO) strategy to enjoy expertise from a supplier without hiring experts. Therefore, ITO gives the bank access to technological skills. Meanwhile, it allows the bank to improve the quality of services, reduce cost, provide flexibility, and focus on core activity. Our aim is to study the main factors that motivate ITO strategic decisions in the banking sector. To answer this inquiry, we develop a conceptual model consisting of four ITO factors corresponding to four hypotheses, which will be tested based on the data collected by a survey performed within a multinational bank. Inspiring by solid and contemporaneous scientific research, we apply a survey within our targeted sample and collect data through email. Our result has shown that majority of responders preconize ITO. They recognize ITO strategic motivation factors as saving cost, allowing access to new technology, and focusing on core business and quality service improvement. Besides those benefits, ITO strategy may arise some risks summarized in this paper. We conclude that a successful ITO alliance enables the bank to achieve a competitive advantage over their competitors.